TO BE RESPONSIBLE SOCIALLY IS VIABLE FINANCIALLY - Iqbal, Danish; Sarwat, Salman; ul Hasan, Shabib; Baloch, Akhtar; Salim, Uzma (European Scientific Journal, ESJ, 2014)
This paper aims to evaluate the impact of Corporate Social Responsibility (CSR) on Company’s Financial Performance (CFP) operating or based in Pakistan. Emerging CSR practices in the developed world have raised question about the inclination of the developing world towards CSR. Pakistan being a developing country, its corporate sector is more concerned about profit maximization than CSR. Various studies around the globe have established that CSR has a positive impact on the financial performance of a company. In this study, secondary data has been used from audited annual reports of 26 companies listed in KSE of similar size from different sectors, which are striving towards better CSR. The data ranges from 2008 to 2012 (5 years). The researchers have used Stakeholder theory to measure CSR; stakeholders include Government, Employees, Suppliers, Creditors, Shareholders and Customers. Return on Asset (ROA) was used as a surrogate for Company’s financial performance (CFP). The result of Multiple Regression Model showed a significant impact of CSR on CFP for only a few stakeholders. After adjusting the model according to Pakistan’s scenario, customers, shareholders and creditors were identified as the key stakeholders for CSR to have an impact on CFP. Analyses also bifurcated the results for KSE 100 index companies and Non KSE 100 index companies in order to have an idea as to how firm size disparity affects CSR’s impact on CFP. The outcomes of the research would be helpful for the corporate decision makers, government policy formulators and other related quarters to understand the impact of CSR on CFP with reference to Pakistan.